Modalitas Calon Bupati Dalam Pemilihan Umum Kepala Daerah Tahun 2015 - Baharuddin, Tawakkal; Purwaningsih, Titin (Journal of Governance and Public Policy, 2017)
In the history of political contestation in South Sulawesi as the election, there has never been a woman who has wonan election. Moreover, the female candidate is a newcomer in the constituency, while his political opponents in theelection are the incumbent. an incumbent is considered to have a greater opportunity than the other candidates,because it is considered to have more capital as the level of popularity and figuritas. Women in the political contestwould also have the same opportunities as other candidates, although the participation of women in a politicalcontest still an issue - an issue that marginalize women. It still can be minimized depending on how the power ofmodality which is owned by the candidates, in which a candidate must have akumalasi more capital so as to win adispute. This study aimed to analyze and learn how modality which is owned by the candidates in the administrationof the election, studies in Indah Putri Indriani as regent elected in the district of North Luwu, South SulawesiProvince Year 2015. The method in this research is qualitative research. The technique of collecting data throughinterviews and documentation. The results of this study found four dominant modality owned by Lovely DaughterIndriani compared to the incumbent candidate. The modality is social capital, cultural, political and economic. Thisproves that the beautiful daughter Indriani as a woman and also newcomers are able to accumulate the capital ithas, so it managed to win a political contest and also became the first female Regent in South Sulawesi.